PENGARUH BEBAN KERJA TERHADAP STRES KERJA PADA PT. HASJRAT ABADI AMBON - Berty Makatita; Elsina Huberta Aponno; Jessy Juniu Hahurya (P3M Politeknik Negeri Ambon, 2023)
Initial survey at PT. Hasjrat Abadi Ambon shows that there are indications of workload problems for employees. On the other hand, employees also show symptoms of work stress. This study aims to determine how the effect of workload on work stress on employees of PT. Hasjrat Abadi Ambon. The analytical method used in this research is descriptive analysis and simple linear regression analysis. Descriptive analysis shows that the workload of the employees of PT. Hasjrat Abadi Ambon with an average value of 2.69 which is interpreted as quite high, while work stress has an average value of 2.92 which is also interpreted as quite high. The results of the regression analysis showed that the workload had a positive effect on the work stress of the employees of PT. Hasjrat Abadi Ambon. Based on these results, it can be concluded that the higher the workload, the higher the employee's work stress. To overcome this, PT. Hasjrat Abadi Ambon must try to reduce the workload by paying attention to the use of working time, targets that must be achieved and working conditions. Employee stress levels must also be reduced by paying attention to employee stress symptoms on psychological, physical, and behavioral indicators. Keywords: workload, work stress Â